2019
DOI: 10.35940/ijitee.j1085.0881019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Domestic Tourist Perceived Risk on Revisit Intention in Malaysia

Abstract: Tourism research identified that the risk element has a significant impact on tourist intention to travel and tourist destination choice criteria. The connection between domestic tourists perceived risk and revisit intention has not been widely explored mainly in Malaysia context, but the existing studies suggest a close connection among them.This study aims to examine the affect tourist perceived risk toward their revisit intention to visit tourist destination in Malaysia. A total of 384 sample valid response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Their findings highlighted that only the physical risk has a significant relationship with the intention to travel. Hashim et al, (2019) investigated the effect of domestic tourist on the perceived risk (physical risk, financial, social, time and psychological) on their intention to visit tourism destination in Malaysia. Their study proved that only the physical and financial risks have an effect on the intention to visit Malaysia.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Their findings highlighted that only the physical risk has a significant relationship with the intention to travel. Hashim et al, (2019) investigated the effect of domestic tourist on the perceived risk (physical risk, financial, social, time and psychological) on their intention to visit tourism destination in Malaysia. Their study proved that only the physical and financial risks have an effect on the intention to visit Malaysia.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Most studies on the topic of tourism during the pandemic simply focus on how perceived COVID-19 related risk affect the industry performance in general or individual behavior (Shin et al 2021 ; Neuburger and Egger 2020 ). For example, prior studies have confirmed that risk, whether physical, psychological, or financial, has a negative impact on travel or revisit intention (An et al 2010 ; Nik Hashim et al 2019 ). Although recent studies have begun to focus on the perceived effectiveness of protective measures, most of these studies simply focus on comparing the effectiveness of different measures and none have yet studied their impact on travel intention (Nakayachi et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that 54 per cent of travellers would return to a destination that offers a safe and comfortable experience (Karl, 2018). In addition, tourist destinations with low potential risks are preferred and will be revisited in the future (Nik Hashim et al, 2019). H3: Fear of COVID-19 influences revisit intention…”
Section: Fear Of Covid-19 and Revisit Intentionmentioning
confidence: 99%